2018
DOI: 10.3390/su10041125
|View full text |Cite
|
Sign up to set email alerts
|

Governing Transactions and Interdependences between Linked Value Chains in a Circular Economy: The Case of Wastewater Reuse in Braunschweig (Germany)

Abstract: Reusing wastewater in agriculture has attracted increasing attention as a strategy to support the transition towards the circular economy in the water and agriculture sector. As a consequence, there is great interest in solutions for governing the transactions and interdependences between the associated value chains. This paper explores the institutions and governance structures for coordinating transactions and interdependences between actors in linked value chains of wastewater treatment and crop production.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 81 publications
(88 reference statements)
1
18
0
Order By: Relevance
“…The quality of the water is also highly valued by the farmers, although it is less valued than river water. It is similar to the case in Germany analyzed by [22]. In this case, they observed that when governance structures are aligned, they rule the reuse of waste-water more efficiently and they increase the value chain of waste-water treatment and crop production.…”
Section: Introductionsupporting
confidence: 71%
“…The quality of the water is also highly valued by the farmers, although it is less valued than river water. It is similar to the case in Germany analyzed by [22]. In this case, they observed that when governance structures are aligned, they rule the reuse of waste-water more efficiently and they increase the value chain of waste-water treatment and crop production.…”
Section: Introductionsupporting
confidence: 71%
“…Within this relational capacity we find the industrial symbiosis that favors the transformation of waste from a process into input or raw material between companies that work together, whether or not they belong to the same industry [44]. This could mean that linking value chains would require new governance structures-incentive intensity, administrative control, autonomous adaptation, and coordinated adaptation-with hybrid and hierarchical characteristics to better face with the interdependencies resulting from current transactions [97].…”
Section: Adaptation Of Logistics and Organizational Managementmentioning
confidence: 99%
“…Interestingly the Main Path concludes by ramifying into two distinguished directions ( Figure 3). Indeed, the latest emerging topics address CE in cities by [73] from Architecture, and the institutions and governance structures role in linked value chains by [74] from Agricultural Engineering. In parallel, the tendency of scholars to review and conceptualize CE still holds through [70] from Sustainability, addressing the inhibitors of CE development in Europe, and [69] from Architecture, Civil Engineering, and Resource Recovery, who explore tools for CE implementation.…”
Section: Main Path Analysismentioning
confidence: 99%